Wealhtheow’s Peace-Weaving: Diegesis and Genealogy of Gender in Beowulf - Olesiejko Jacek (Studia Anglica Posnaniensia, 2014)
This article uses Charles S. Peirce’s concept of icon and Judith Butler’s idea of genealogy of gender to study levels of fictionality in the Old English poem Beowulf. It shows that Wealhtheow, the principal female character in the epic, operates as a diegetic reader in the poem. Her speeches, in which she addresses her husband King Hrothgar and Beowulf contain implicit references to the Lay of Finn, which has been sung by Hrothgar’s minstrel at the feast celebrating Beowulf’s victory. It is argued here that Wealhtheow represents herself as an icon of peace-weaving, as she casts herself as a figuration of Hildeburh, the female protagonist of the Lay of Finn. Hildeburh is the sister of Hnæf, the leader of the Danes, and is given by her brother to Finn the Frisian in a marriage alliance. In her role as a peace-weaver, the queen is to weave peace between tribes by giving birth to heirs of the crown. After the courtly minster’s performance of the Lay, Wealhtheow warns her husband against establishing political alliances with the foreigner Beowulf at the expense of his intratribal obligation to his cousin Hrothulf, who is to become king after Hrothgar’s death.